ABREVIAÇÃO DO JEJUM PRÉ-OPERATÓRIO: PROTOCOLO MULTIMODAL BASEADO EM EVIDÊNCIA - Azevedo, Samara Cléssya Lucena de; Campos, Samara Bomfim Gomes; Meira, Júnia Elisa Carvalho de; Guedes, Glaucevane da Silva (Gep News, 2017)
Tipo de Apresentação: Comunicação Oral